ANALISIS STRATEGI PENGEMBANGAN REKAM MEDIS ELEKTRONIK DI INSTALASI RAWAT JALAN RSUD KOTA YOGYAKARTA - Muhammad Hamdani Pratama; Sri Darnoto (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2017)
Although developing countries are still concernin handling various infectious diseases but effective and efficienthealth care documentation process is needed (Kalogriopoulos et all, 2009). The implementation of electronic medical record (EMR) is a solution for effective and efficient documentation. Support of the electronic and transaction laws and Ministri of Health Regulation No.269 in year of2008 bright hope for the development of EMR. Provision of medical record file is still a problem in Yogyakarta General Hospital. In addition, medical records storage space is over capacity. Optimizing of medical records service provision need to be reviewed to minimize the use of paper and time efficiency.The purpose of this study was to analyze the development strategies outlined by EMR readiness analysis used instruments of DOQ-IT (Doctor's Office Quality-Information Technology) and strategy analysis used SWOT (Strengths, Weakness, Opportunities, Treats) instrument. This study used concurrent mix methode. Subjects in this study were 40 people who are the decision makers and users of EMR in Outpatient Installation of Yogyakarta General Hospital. The collection of data through interviews and questionnaires. The results showed that the Yogyakarta General Hospital in the moderately prepared category for EMR development. The results of the strategy analysis showed that Yogyakarta General Hospitals included in II quadrant, which showed a strong organization but faces many threats to develop EMR. The recomendation for thestrategies is diversification strategy.